資訊科技應用於數學科教學之探討 Exploration on Integrating Information Technology into Mathematics Instruction - Shu-Chuan Chung; Jing-Tz Cheng (Jiàoyù zīliào yǔ túshūguǎn xué, 2005)
本文主要針對資訊科技融入數學教學的各面向做探究，分別從：一、數學教學的困境與相關的對策；二、資訊科技融入數學教學的功能；三、資訊科技融入數學教學的教學策略；四、資訊科技融入數學教學的限制；五、人員、教材、教法和設備的配合；最後，希望提出「多看、多聽、多學習」的方式，期許資訊融入數學教學能夠達成師生「教、學」雙贏的目標。 The main purpose of this article is to explore five aspects of integrating information technology into mathmatics instruction. The following five aspects are：1.problems and solutions of mathematics instruction; 2.functions of integrating information technology into mathematics instruction; 3.strategy of integrating information technology into mathematics instruction; 4.restrictions of integrating information technology into mathematics instruction; 5.the preparation of aspects such as people, materials, methods and facilities. Focusing on above theses, integrating information technology into mathematics instruction can fulfill the goal of “best teaching and best learning”.